Frege in Perspective - Weiner, Joan (Book collections on Project MUSE., 1990)
"What is the number one? How do we know that 2 + 2 = 4? These apparently simple questions are in fact notoriously difficult to answer, and in one form or other have occupied philosophers from ancient times to the present. Gottlob Frege's conviction that the truths of arithmetic, and mathematics more generally, are derived from self-evident logical truths formed the basis of a systematic project which revolutionized logic, and founded modern analytic philosophy." "In this introduction, Joan Weiner traces the development of Frege's thought from his invention of a powerful new logical language in Begriffsschrift, through his explication of his project in the Foundations of Arithmetic and famous papers such as 'On Sense and Meaning', to the brilliant, but ultimately doomed, presentation of the system in Basic Laws of Arithmetic."--Jacket